Legal Aspects Related To Information Security In E-Commerce - Darmawan Sutawijaya (PT. Anagata Sembagi Education, 2024)
Legal protection concerning information security and personal data in Indonesia continues to evolve. While regulations such as the Electronic Information and Transactions Law (UU ITE) and Personal Data Protection regulations exist, their enforcement and effectiveness are still limited. Weak law enforcement, coupled with low public awareness, pose significant challenges to protecting e-commerce consumers. Additionally, the rapid advancement of technology often outpaces regulatory adjustments, creating a gap in ensuring comprehensive information security. This study employs a normative legal method, utilizing secondary data analysis from legal documents and relevant literature. The findings indicate that while a solid legal framework is in place, the implementation remains insufficient. To address this, adaptive regulatory updates, increased supervision, and enhanced law enforcement are imperative. Furthermore, collaboration between the government, industry stakeholders, civil society, and educational initiatives are crucial in promoting consumer awareness and safeguarding personal data. This holistic approach aims to strengthen legal protection for information security in the e-commerce sector, fostering a safer and more secure digital environment.